The Role of ERP Systems in Changing Business Processes - Belak, Stipe; Ušljebrka, Ivana (Oeconomica Jadertina, 2017)
This paper discusses the role that the ERP system has in the radical and continuous change of business processes. The radical change in business processes entails a radical modification, more precisely the termination of the existing method of doing business. Such a dramatic change is needed when the performance of the organization has decreased dramatically, and in order to gain a competitive advantage. However, due to frequent changes in the market and pressures to lower prices, better the quality, provide faster delivery, and the like, the once achieved competitiveness can be sustained long term only through continuous adjustments and improvements of business processes. What follows is the importance to constantly monitor and analyze the business processes in order to properly address the changes. Since there are a multitude of business processes within an organization that are connected to each other, and which intersect the functional and organizational boundaries, their monitoring is enabled only through the integrated information system such as ERP. Therefore the purpose of this paper is to examine what is the role of the mentioned system during the implementation of the changes in the business process. The paper concludes that the ERP system acts as an initiator of a radical redesign of business processes, but also as a facilitator of both a radical redesign and a continuous improvement of business processes. Given that any business change demands an adaptation of the information system, what follows is that it is necessary to change the business processes simultaneously with the introduction/modification of the ERP systems.
Keywords: ERP system; business process; a radical redesign of business processes (BPR); the continuous improvement of business processes (TQM)